Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises - Page 21: 46



Work Step by Step

$4y^{2}-4xy+x^{2}$ =$4y^{2}-2xy-2xy+x^{2}$ =$2y(2y-x)-x(2y-x)$ $(2y-x)(2y-x)$$=0$ $(2y-x)^{2}$$=0$ y=$\frac{x}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.